The Development Features and Design of a Vibratory Gyroscope with a Metallic Cylindrical Resonator - CHIKOVANI, Valerii; HOLOVACH, Serhii; STROKACH, Hryhorii; AVRUTOV, Vadym (Engineering Transactions, 2025)
This paper presents the results of developing a vibratory gyroscope with a cylindrical resonator made of Elinvar alloy. The vibratory gyroscope operates in three modes. These modes include rate mode, rate-integrating mode, and a new, third, differential mode. The differential mode can simultaneously measure two opposite angular rates, Ω and −Ω. A block diagram of the standing wave control system for each mode is presented. The advantages and disadvantages of each of the modes are analyzed. A triple-mode gyro is proposed. The results of experimental studies and simulation data are also presented.